Pediatric renal mass or xanthogranulomatous pyelonephritis? - Tiernan Connor Middleton; Dennis Drehner; Monica Epelman; Tamarah J. Westmoreland; Adela Casas-Melley; Pamela Ellsworth (Elsevier, 2020)
Renal masses in the pediatric population carry a wide differential diagnosis; however, a careful history and physical can often elucidate the source. Infectious, benign, and malignant causes should all be considered in a patient presenting with a renal mass to mitigate risks of treatment options and safely ameliorate the patient's pathology. Pediatric renal masses are rare. Renal malignancies in the pediatric population generally present with a painless, enlarging abdominal mass without the classic B symptoms of fevers, chills, or night sweats. Patients with infectious causes such as pyogenic abscesses or renal tuberculosis classically present as acutely ill with fevers, chills, night sweats, pain, and hematuria. These patients also often have a past medical history of previous urinary tract infections and anatomic pathologies such as vesicoureteral reflux, posterior urethral valves, duplex collecting systems, megaureter, or ectopic ureters. Xanthogranulomatuos pyelonephritis, an uncommon condition in children typically is seen in the setting of obstruction, infection and stones. In the absence of such indicators, the diagnosis is elusive. The presence of pyrexia and elevated inflammatory markers may help with the diagnosis in the absence of infection, obstruction, stones. The management of which, varies with the severity of illness and extent of involvement of the kidney. Keywords: Renal mass, Wilms tumor, Xanthogranulomatous pyelonephritis